Dental manifestations of a paediatric patient with Goldenhar syndrome: a case report - Al Ghamdi, Sara Ayid (Journal of the Pakistan Medical Association, 2022)
Goldenhar syndrome (GS) is a rare congenital disorder. It arises from the first pharyngeal pouch, first branchial cleft, first and second branchial arches, and primordia of the temporal bone. It mainly involves abnormalities in the ear, mandibular, and maxillary arches, and is associated with variable clinical features such as skeletal, cardiac, and renal systems. The presence of extra teeth in the dental arch is called supernumerary teeth, and hypodontia refers to congenitally missing teeth. The occurrence of both these anomalies in the same patient is called concomitant hypohyperdontia. However, the GS itself is not very rare, though the presence of concomitant hypohyperdontia has not been reported. The purpose of the present case report is to describe the first case from Saudi Arabia with a characteristic combination of rare findings in a seven-year-old child with comprehensive oral rehabilitation. Keywords: Goldenhar syndrome, anomalies, dental treatment.